Posisi Semi Fowler untuk Meningkatkan Saturasi Oksigen pada Pasien dengan Chronic Kidney Disease di Intensive Care Unit - Farel Stepanus Subagiartha; Mulyadi Mulyadi; Reginus Tertius Malara (FORIKES, 2024)
Chronic kidney disease is a gradual decline in kidney function over a long period of time and will worsen over time. Approximately 83% of patients treated at the Intensive Care Unit of R.D. Kandou Hospital experience respiratory failure, while the rest have a history of respiratory failure and 50% of them are diagnosed with chronic kidney disease. This study aimed to analyze nursing care by providing a semi-fowler position in patients with chronic kidney disease with nursing problems of impaired gas exchange. This study was conducted in the form of a case report with a patient. The intervention given was in the form of positioning (semi-fowler) which was implemented for 3 days, accompanied by measurement of peripheral capillary oxygen saturation (SpO2). The patient used an oximeter when providing a semi-fowler position or when there was a change in position in the patient. Based on the evaluation results, it was found that on the second day of providing a semi-fowler position, oxygen saturation increased and was optimal in 14 minutes. On the intervention on the third day, oxygen saturation increased and was optimal in 12 minutes. Furthermore, it was concluded that the semi-fowler position can increase oxygen saturation in patients with chronic kidney disease with impaired gas exchange problems.Keywords: chronic kidney disease; respiratory failure; intensive care unit; oxygen saturation; semi fowler ABSTRAK Chronic kidney disease merupakan penurunan fungsi ginjal yang terjadi secara bertahap dalam waktu yang lama dan akan semakin parah seiring berjalannya waktu. Sekitar 83% pasien yang dirawat di Intensive Care Unit Rumah Sakit R.D. Kandou mengalami gagal napas, sedangkan sisanya dengan riwayat gagal napas dan 50% di antaranya terdiagnosis chronic kidney disease. Studi ini bertujuan untuk menganalisis asuhan keperawatan dengan pemberian posisi semi fowler pada pasien chronic kidney disease dengan masalah keperawatan gangguan pertukaran gas. Studi ini dilakukan dalam bentuk case report dengan seorang pasien. Intervensi yang diberikan berupa pengaturan posisi (semi fowler) yang diimplementasikan selama 3 hari, diiringi dengan pengukuran saturasi oksigen kapiler perifer (SpO2). Pasien menggunakan oksimeter pada saat pemberian posisi semi fowler maupun saat terjadi perubahan posisi pada pasien. Berdasarkan hasil evaluasi didapatkan bahwa pada pemberian posisi semi fowler hari kedua, saturasi oksigen meningkat dan optimal dalam 14 menit. Pada intervensi pada hari ketiga, saturasi oksigen meningkat dan optimal dalam 12 menit. Sejanjutnya disimpulkan bahwa posisi semi fowler dapat meningkatkan saturasi oksigen pada pasien chronic kidney disease dengan masalah gangguan pertukaran gas.Kata kunci: chronic kidney disease; gagal napas; intensive care unit; saturasi oksigen; semi fowler